Autonomic Dysfunction in Asian Indian T2DM Patients is Related to Body Fat Content Instead of Insulin Resistance: A DEXA Study - Poonam Punjabi; Prashant Mathur; R.C. Gupta; Itisha Mathur; Jyoti Thanvi; Deepak Gupta; Sandeep Mathur (Journal of Basic & Applied Sciences, 2014)
Aim: To study autonomic dysfunction in Asian Indian T2DM patients by heart rate variability and it’s relation with body fat content, distribution and insulin resistance. Subjects and Methods: Subjects: 33 T2DM patients aged (46.96 ± 8.90 yrs), and 33 healthy controls aged (44.08 ± 9.15 yrs). Methods: Short-term heart rate variability (HRV) was measured by impedance plethysmograph recording of pulse wave in distal superficial arteries. Time domain and Frequency domain analysis of HRV was carried out. Time domain parameters (SDNN, rMSSD, pNN50) and frequency domain parameters (Total Power, LF power, HF Power, LF (nu), HF (nu), LF/HF Ratio) were determined. Body fat content and distribution was estimated by (DEXA). Insulin Resistance was assessed by HOMA-R. Student t test was used for comparison of parameters in two groups. Multiple regression was used to find out relation between parameters of adiposity and HRV. Results: Parameters rMSSD, pNN50, Total power, LF Power, HF Power were significantly lower in diabetics. Total power showed negative correlation with BMI and truncal fat (r=-.43; p<. 05) and (r=-.41; p<. 05) respectively. Frequency domain parameter HF (ms2) showed negative correlation with BMI and trunk fat (gm %) (r= -.47; p<. 05) and (r=-.40; p<. 05) respectively. HF (nu) was negatively correlated with BMI (r=-.43; p<. 05) whereas positive correlation was observed between LF (nu) and BMI (r=. 40; p<. 05). Conclusion: T2DM is associated with overall reduction in autonomic activity however, body fat content influences relative modulation of sympathetic and parasympathetic activity among diabetics but not among controls. Contrary to most previous reports, insulin resistance as well as W: H ratio had no influences on autonomic activity.